A blueprint for success in real-world evidence: “glocal” approach to building capabilities and generating impactful evidence - Larsen, Kristoffer; Walton, Ryan N.; Elsayed, Mohamed; Ipatov, Andrey; Townsend-Holyoake, Faye; Axelsson, Sebastian F. A.; Quinones, Nacho; Papsch, Rudiger; Givens, Jennifer; Bedenkov, Alexander; Seewald, Michael (Frontiers in Pharmacology, 2023)
The past decade has seen the increasing influence and relevance of real-world data (RWD) and realworld evidence (RWE) in healthcare decision making. The value added by RWD/RWE has prompted the pharmaceutical industry to develop high performing systems and practices to harness the power of evidence generated at the global level. However, this worldwide transformation provides outstanding opportunities to support capability building within local affiliates and to impact key country-level stakeholders through resulting evidence.Therefore, we present an Evidence Blueprint Initiative, which links the global and local ('glocal') skills, and furthermore addresses the opportunities and gaps in evidence generation capabilities at manuscript. The thoughts and statements expressed within this article are written in the capacity of healthcare professionals and not as AstraZeneca or IQVIA employees.